Disrupting cisnormativity: Decentering gender in families (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2019)
Within the last decade, emerging research and activism in the sphere of transgender and gender non-binary (TGNB) persons has necessitated new vocabulary and perspectives. Families of TGNB are often challenged to reevaluate understandings of gender, of sexuality, and the family unit itself. Gender binaries are perpetuated and reinforced in Western culture through our gender “performances” (Butler, 2004), and children are judged on their performances (Wahlig, 2015). The conceptual model of decentering cisnormativity allows researchers to analyze when tensions grow taut when society members are confronted with gender nonconformity. Parents often undergo transformation when they choose to explore these tensions, deconstruct their assumptions about gender, and critically reflect on their underlying biases, belief systems, values, and understandings. In this way, it is not only TGNB children who transition, but those around them (Malpas, 2017) as their belief systems and social constructions of gender are called into question.